Rancangan Sistem Informasi Pengendalian Kualitas Produk Barrel pada PT OneJect Indonesia dengan Metode Six Sigma - Sudirwan, J.; L., M. Marciano (Bina Nusantara University, 2013)
PT OneJect Indonesia faces the high level of defect on its barrel products. To overcome this problem, this study proposes an application quality control based on information system. We implement requirement analysis based on the needs of quality control methods, while to lower the defect rate we utilize Six Sigmamethod with DMAIC (define, measure, analyze, improve, control) phases. In define phase we determine the type of product to be investigated using Critical to Quality, as well as the problems and objectives. In measure phase we calculate DPMO value and sigma level; sigma value of 3.520 is obtained. Then we calculate P control chart to see the production process control. In analyze phase we create pareto diagram to see the types of dominant defects. Then we create cause-and-effect diagram to determine the cause of defects, and five whys diagram to determine the root causes of the defects. In improve phase, we do improvement analysis through FMEA table by calculating the RPN value to determine the failure modes to be controlled. In control phase, we implement the proposal and simulation of sigma value increase. The analysis and design uses object-oriented information system by Lars Mathiasen, and UML as the requirement modeling and the design system. The results obtained are the documents of top-level analysis and design of information system as a quality control material for the actual system development.